2012
DOI: 10.1371/journal.pone.0036180
|View full text |Cite
|
Sign up to set email alerts
|

Call Cultures in Orang-Utans?

Abstract: BackgroundSeveral studies suggested great ape cultures, arguing that human cumulative culture presumably evolved from such a foundation. These focused on conspicuous behaviours, and showed rich geographic variation, which could not be attributed to known ecological or genetic differences. Although geographic variation within call types (accents) has previously been reported for orang-utans and other primate species, we examine geographic variation in the presence/absence of discrete call types (dialects). Beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 57 publications
3
71
0
1
Order By: Relevance
“…Indeed, the geographic patterning of presence or absence of leaf kiss-squeaks is neither sufficiently explained by genetic differentiation between populations nor environmental differences [3]. This observed variation concurs with evidence demonstrating that genetic differentiation does not sufficiently explain the geographic pattern of other orangutan calls [15]. Conversely, orangutans have been empirically shown capable of observational learning [38].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Indeed, the geographic patterning of presence or absence of leaf kiss-squeaks is neither sufficiently explained by genetic differentiation between populations nor environmental differences [3]. This observed variation concurs with evidence demonstrating that genetic differentiation does not sufficiently explain the geographic pattern of other orangutan calls [15]. Conversely, orangutans have been empirically shown capable of observational learning [38].…”
Section: Discussionmentioning
confidence: 70%
“…First, a signal (with its respective function) may be present in one population but absent in another population (birds [5]:, bats [6]:, pinnipeds [7,8]:, cetaceans [9,10]:, nonhuman primates [11,12]:). Second, acoustically distinct signals with a similar function may be present in different populations (birds [13]:, cetaceans [14]:, nonhuman primates [4,15]:); such examples further imply that the signal’s acoustic structure is arbitrary. In other words, there is no particular relationship between the signal’s internal/external determinants (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Among orangutans, for example, van Schaik, Wich and their colleagues have demonstrated that three calls, raspberries, kiss squeak with hands, and kiss squeak with leaves, are patchily distributed among disparate study populations (van Schaik et al 2003;Wich et al 2012). For example, raspberries, which are bilabial fricatives associated in this species with nest-building, are reportedly absent from four of six sites studied, but present in two sites, one on the island of Sumatra the other on Borneo (van Schaik et al 2003).…”
Section: Evidence From Patchy Distribution Of Callsmentioning
confidence: 94%
“…Nests were determined through purposive sampling method based on the information of community and staff of national parks. Nests are relatively easy to find since orangutans make nests every day (Wich et al 2012a). The research site was determined by considering the condition of location that can represent the area of the research site.…”
Section: Methodsmentioning
confidence: 99%
“…This area has also been designated as a strategic area district (kawasan strategis kabupaten) which is very important in terms of environmental concerns. One of the important fauna that exists in this region and national park is the bornean orangutan (Pongo pygmaeus), which also has become a global conservation icon (Wich et al 2012a).…”
Section: Introductionmentioning
confidence: 99%